Anti-NMDAR antibodies, the blood–brain barrier, and anti-NMDAR encephalitis - Gong, Xiarong; Wang, Niya; Zhu, Hongyan; Tang, Ning; Wu, Kunhua; Meng, Qiang (Frontiers in Neurology, 2023)
Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is an antibody-related autoimmune encephalitis. It is characterized by the existence of antibodies against NMDAR, mainly against the GluN1 subunit, in cerebrospinal fluid (CSF). Recent research suggests that anti-NMDAR antibodies may reduce NMDAR levels in this disorder, compromising synaptic activity in the hippocampus. Although anti-NMDAR antibodies are used as diagnostic indicators, the origin of antibodies in the central nervous system (CNS) is unclear. The blood–brain barrier (BBB), which separates the brain from the peripheral circulatory system, is crucial for antibodies and immune cells to enter or exit the CNS. The findings of cytokines in this disorder support the involvement of the BBB. Here, we aim to review the function of NMDARs and the relationship between anti-NMDAR antibodies and anti-NMDAR encephalitis. We summarize the present knowledge of the composition of the BBB, especially by emphasizing the role of BBB components. Finally, we further provide a discussion on the impact of BBB dysfunction in anti-NMDAR encephalitis.